Contribution of Climate-Smart Forage and Fodder Production for Sustainable Livestock Production and Environment: Lessons and Challenges from Ethiopia - Diriba Tulu; Sileshi Gadissa; Feyisa Hundessa; Erana Kebede (Advances in Agriculture)
Sustainable farm animal raising is dependent on the production of sufficient quantities and quality of forages and fodder, especially in dry regions. Improved forage and feed species are an option for these aspects because adequate feed resources enhance soil health and carbon, generate income, and reduce emissions. Therefore, the purpose of this review paper was to investigate the role of climate-smart forage production in sustaining farm animal production and maintaining the environment in arid and semiarid regions. Seasonal fluctuations in feed supply cause temporal scarcity in Ethiopia, with more acute gaps in dry periods, particularly in drought-prone regions. To address these problems in the country, improve forages to strengthen farm productivity, climate change resilience, and environmental sustainability, particularly in arid and semiarid areas. The country has a long history and is of some exemplary practices in indigenous improved forage production, but the input of improved forage to the total biomass production in feed resources is still low due to many factors like scarcity of land and water for irrigation, lack of awareness, forage seed, and policy recommendations. Despite the potential profits of feed and forage grasses and legumes, the availability of species adapted to a wide range of situations in actual use in the livestock sector has been insufficient. Therefore, it is strongly suggested that climate-resilient forage species be popularized to sustain livestock production and the environment, particularly in the country’s arid and semiarid regions.